Suppression of intervalley exchange coupling in the presence of momentum-dark states in transition metal dichalcogenides - Malte Selig; Florian Katsch; Samuel Brem; Garnik F. Mkrtchian; Ermin Malic; Andreas Knorr (Physical Review Research, 2020)
Monolayers of transition metal dichalcogenides (TMDCs) are promising materials for valleytronic applications, since they possess two individually addressable excitonic transitions at the nonequivalent K and K^{′} points with different spins, selectively excitable with light of opposite circular polarization. Here, it is of crucial importance to understand the elementary processes determining the lifetime of optically injected valley excitons. In this study, we perform microscopic calculations based on a Heisenberg equation of motion formalism to investigate the efficiency of the intervalley coupling in the presence (W-based TMDCs) and absence (Mo-based TMDCs) of energetically low-lying momentum-dark exciton states after pulsed excitation. While we predict a spin polarization lifetime on the order of some hundreds of femtoseconds in the absence of low-lying momentum-dark states, we demonstrate a strong elongation of the spin-polarization lifetime in the presence of such states due to a suppression of the intervalley exchange coupling.